IMPLEMENTASI METODE VALUE STREAM MAPPING PADA INDUSTRI: TINJAUAN LITERATUR SISTEMATIS - Setiawan, Bambang; Setiawan, Indra; Kurnia, Hibarkah; Wahid, Muhammad; Purba, Humiras H. (Teknik Industri Unikom, 2022)
Value Stream Mapping (VSM) is a method of Lean Manufacturing to identify and reduce waste in the entire industrial process. VSM has been applied to various fields of the manufacturing industry and even to the service sector. A systematic review of the VSM literature is needed, to provide information about the implementation of VSM that has been carried out for further research. This study aims to analyze and explore more deeply related to VSM applications in industry. This study uses the Systematic Literature Review method. The identified literature includes 50 selected articles based on selection. The articles collected were based on 45 Indonesian articles and 5 international articles, with a publication range from 2010 to 2020. The application of VSM found was dominated by the automotive industry. The benefits of implementing VSM from the entire literature found include waste elimination and reduction, process time and cost efficiency, quality improvement and industrial productivity improvement. However, there is some literature related to VSM that only focuses on one goal, so it has not received the overall benefit.